Emory-Tibet Science Initiative: Changes in Monastic Science Learning Motivation and Engagement During a Six-Year Curriculum - Gray, Kelsey M.; Achat-Mendes, Cindy; Kruger, Ann Cale; Lhamo, Tashi; Wangyal, Rinchen; Gyatso, Gelek; Worthman, Carol M. (Frontiers in Communication, 2022)
Led by His Holiness the Dalai Lama, the initiative taken by the Tibetan Buddhist monastic community to connect with western science and scientists presents a unique opportunity to understand the motivations and engagement behaviors that contribute to monastic science learning. In this study, we draw on quantitative data from two distinct surveys that track motivations and engagement behaviors related to science education among monastic students. The first survey was administered at one monastic university in 2018, and the second follow-up survey was completed by students at two monastic universities in 2019. These surveys assessed the reception of science education related to motivations among monastics and their demonstration of engagement-with-science behaviors. We also tested for variation over time by surveying students in all years of the science curriculum. We identified that monastic students are motivated by their perception that studying science has an overall positive effect and benefits their Buddhist studies, rather than negatively affecting their personal or collective Buddhist goals. In accordance with this finding, monastics behave in ways that encourage fellow scholars to engage with science concepts. Survey responses were disaggregated by years of science study and indicated changes in motivation and engagement during the six-year science curriculum. These insights support the relevance of considering motivation and engagement in a novel educational setting and inform ongoing work to expand the inclusiveness of science education. Our findings provide direction for future avenues of enhancing exchange of knowledge and practice between Buddhism and science.